2021
DOI: 10.1111/wrr.12978
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing lower extremity amputation outcomes in people with active foot ulceration in regional Australia: A retrospective cohort study

Abstract: Australia has the second highest rate of non-traumatic lower extremity amputation (LEA) globally. Australia's large geographical size is one of the biggest challenges facing limb preservation services and may be contributing to LEA. The aim of this study was to determine what factors contribute to the likelihood of LEA in people with active foot ulceration in regional Australia. This retrospective cohort study audited patients with active foot ulceration in a multidisciplinary high risk foot service (HRFS) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The benefits of multidisciplinary specialised care are well known and it is generally accepted that specialised coordinated care is both economical and effective in reducing complications associated with DFD 41–44 . Despite this evidence, not all Australians have access to this care, which is partly responsible for the higher rates of DFD‐related amputation seen in individuals who live greater distances from care 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of multidisciplinary specialised care are well known and it is generally accepted that specialised coordinated care is both economical and effective in reducing complications associated with DFD 41–44 . Despite this evidence, not all Australians have access to this care, which is partly responsible for the higher rates of DFD‐related amputation seen in individuals who live greater distances from care 6 …”
Section: Discussionmentioning
confidence: 99%
“…The Australian Institute of Health and Welfare statistics demonstrate a 50% higher likelihood of lower limb amputation for people who reside in rural areas, 23 with similar findings demonstrated by other local studies. 6,24,25 However, the cause of poorer health outcomes in rural areas is complex. Poor health is multifactorial and is often driven by social determinants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, where possible, automated measures were used to reduce the risk of measurement error. Geographical distance from participant residence to their high‐risk foot service was not accounted for and should be considered a limitation, as previous studies have demonstrated that increased geographical distance from specialised care is associated with an increased likelihood of amputation 73 . Similarly, the number of clinical appointments attended from baseline throughout the study period was not included and this should also be considered a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Australia has been reported to have higher DFD‐related hospitalisation and amputation rates than similar countries [ 7 , 8 , 9 ]. However, substantial variation exists between different geographical areas within Australia and also within indigenous populations [ 10 , 11 , 12 ]. It is estimated that on any given day in Australia, 50,000 people have DFD, 1000 are in hospital due to DFD, 12 will undergo a DFD‐related amputation and four people will die due to DFD [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%